Determination of Total Flavonoid Content in Ethanolic Leaf Extract of Calotropis gigantea: A Comparison Between Geothermal and Non-Geothermal Areas - Karma, Taufiq (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Calotropis gigantea (L.), commonly known as biduri, is a plant recognized for its pharmacological properties, including antioxidant and anti-inflammatory activities, largely attributed to its secondary metabolites, particularly flavonoids. The concentration of these bioactive compounds is strongly influenced by the environmental conditions in which the plant grows. Geothermal manifestation areas, characterized by extreme abiotic conditions, can induce metabolic responses in plants, potentially enhancing flavonoid production. This study aimed to determine and compare the total flavonoid content in ethanolic leaf extracts of C. gigantea collected from geothermal and non-geothermal areas in Aceh Province. Extraction was conducted using 96% ethanol, and total flavonoid content was quantified using UV-Vis spectrophotometry via the aluminum chloride (AlCl₃) complexation method. Quercetin served as the standard, and flavonoid levels were expressed as milligrams of quercetin equivalents per gram of extract (mg QE/g). The calibration curve showed a linear relationship between quercetin concentration and absorbance, with a regression equation of y = 0.0101x – 0.0098 (r = 0.9417). The results demonstrated significant differences in flavonoid content between samples from geothermal and non-geothermal sites. C. gigantea plants from geothermal areas exhibited altered flavonoid levels compared to those from non-geothermal regions, indicating that environmental factors play a role in modulating the biosynthesis of these bioactive compounds.